THE INTER-AMERICAN COURT OF HUMAN RIGHTS: THE AMBASSADOR OF UNIVERSALISM - Hennebel, Ludovic (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2011)
The Inter-American Court of Human Rights has developed an original, creative, avant-garde and even “legally non-conformist” jurisprudence. The Court takes certain liberties with regard to the way in which it interprets the American Convention, treating the State-centric paradigm and voluntarism with disdain and consequently risks displeasing member States and internationalist scholars. However, the Court adopts this attitude intentionally and asserts the Inter-American distinctiveness through its own construction of legal universalism. In order to analyse it, the paper will describe the Court's work through the prism of a number of problems, emphasizing the most salient characteristics of this “Inter-American doctrine”: individualization; criminilization; constitutionalization; humanization; and moralization of inter-American law.